Public health in the British empire : intermediaries, subordinates, and the practice of public health, 1850-1960 - Johnson, Ryan, 1975-; Khalid, Amna, 1979- (New York : Routledge, 2012)
"Over the last several decades, historians of public health in Brita in colonies have been primarily concerned with the process of policy ma king in the upper echelons of the medical and sanitary administrations. Yet it was the lower level staff that formed the backbone of public he alth systems in the colonies. Although they constituted the bases of ma ny colonies public health machinery, there is no consolidated study of these individuals to date. Public Health in the British Empire addresse s this gap by bringing together historians studying intermediary and su bordinate staff across the British Empire.Along with investigating the duties and responsibilities of medical and non-medical intermediary and subordinate personnel, the contributors to this volume show how the su bjectivity of these agents influenced the manner in which they discharg ed their duties and how this in turn shaped policy. Even those working as low level assistants and aids were able to affect policy design. In this way, Public Health in the British Empire brings into sharp relief the disaggregated nature of the empire, thereby challenging the underst anding of the imperial project as an enterprise conceived of and driven from the center"--
Includes bibliographical references and index.
Keywords: Public health -- Great Britain -- History -- 19th century; Public health -- Great Britain -- History -- 20th century; HISTORY / Europe / Great Britain; HISTORY / Modern / 19th Century; HISTORY / Modern / 20th Century